Legal Liability of Subsidiaries For Unlawful Actions Committed By The Parent Company (Holding Company) In The Structure of A Limited Liability Company - Saputra, Hendrik (Dinasti Research, 2025)
The group structure of a company consisting of a holding company and a subsidiary company is often used in the business world to expand business activities and manage business risks. In the Indonesian legal system, each limited liability company has the status of an independent legal entity, which means that the legal responsibility of one entity is not necessarily imposed on another entity. However, problems arise when the parent company commits unlawful acts and causes losses, especially if the subsidiary is considered to be involved or a means of implementing the action. This study aims to analyze the extent to which subsidiaries can be held legally liable for unlawful actions committed by the parent company in the limited liability company structure. The method used is normative juridical with relevant legislative approaches, legal doctrines, and case studies. The results of the study show that although the principle of separate legal entities is still recognized, the court can pierce the corporate veil if evidence is found of the dominance of the parent company over the subsidiary as a whole, as well as the involvement of the subsidiary in the unlawful act. Thus, under certain conditions, the subsidiary can be held legally liable if it is proven to have a substantial close relationship with the parent company in the implementation of unlawful actions. These findings reinforce the importance of a strict separation of responsibilities in the corporate group structure, in order to ensure legal certainty and protection for aggrieved third parties.